The Level of Public Knowledge About the Treatment of Gastritis at The Kyan Sehat Pharmacy - Karimah, Dian Sarirotul; Efendi, Jamaludin Al Jamaludin (CV. Nusantara Scientific Medical, 2023)
Gastritis is an inflammatory condition of the gastric mucosa, which can be acute or chronic, with a very high number of sufferers in Indonesia. Public knowledge and awareness about gastritis is still lacking, one of which is the adoption of an unhealthy lifestyle. If left continuously, it will damage the function of the stomach and will increase the risk of getting gastric cancer which can lead to death. This research was able to find out “Level of Public Knowledge About Gastritis Treatment at the Kyan Sehat Pharmacy”. This type of research is observational by making descriptive observations, The data taken is done quantitatively. The data collected is in the form of quantitative data. This study describes how the level of public knowledge about the treatment of gastritis, explore the relationship between the level of knowledge and self-medication behavior using a survey method with a questionnaire as the main instrument. The results show that the level of knowledge of the respondents regarding the treatment of gastritis is 55% which is a good category, the sufficient category is 40% and the less category is 5%. And gastritis treatment behavior obtained data as much as 17% have gastritis (ulcer) treatment behavior which is in the good category, for the sufficient category, namely 70%, and the less category, namely 13%. So knowledge about gastritis (ulcer) treatment has good knowledge, namely as much as 55% and gastritis (ulcer) treatment behavior has sufficient behavior as much as 70%